2013
DOI: 10.1021/jp406776x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Azole Compounds with DOPC and DOPC/Ergosterol Bilayers by Spin Probe EPR Spectroscopy: Implications for Antifungal Activity

Abstract: The influence of two antifungal azoles, the newly synthesized compound CPA18 and the commercial drug fluconazole (FLC), on the physical state of 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) and DOPC/ergosterol bilayers was investigated by spin probe electron paramagnetic resonance (EPR) spectroscopy with the aim of ascertaining if direct interactions with the plasma membrane are implied in the mechanism of action against Candida albicans . 5- and 16-Doxyl-stearic acids (5-DSA and 16-DSA, respectively) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…In fungi, the main sterol ergosterol has important roles in controlling membrane fluidity 55,56 and supporting the activity of PM enzymes 57 . Consequently, depletion of ergosterol is widely thought to compromise the integrity of the PM 14,15 , and it was suggested that this underpins the fungicidal activity of certain azole compounds 58 . In this study, we use a fluorescent PM syntaxin GFP-Sso1 24 and show reduces membrane fluidity in azoletreated Z. tritici cells, a result that is consistent with findings in C. glabrata 59 .…”
Section: Discussionmentioning
confidence: 99%
“…In fungi, the main sterol ergosterol has important roles in controlling membrane fluidity 55,56 and supporting the activity of PM enzymes 57 . Consequently, depletion of ergosterol is widely thought to compromise the integrity of the PM 14,15 , and it was suggested that this underpins the fungicidal activity of certain azole compounds 58 . In this study, we use a fluorescent PM syntaxin GFP-Sso1 24 and show reduces membrane fluidity in azoletreated Z. tritici cells, a result that is consistent with findings in C. glabrata 59 .…”
Section: Discussionmentioning
confidence: 99%